Full-Endoscopic Lumbar Discectomy Approach Selection: A Systematic Review and Proposed Algorithm. Issue 8 (15th April 2023) - Kotheeranurak, Vit; Liawrungrueang, Wongthawat; Quillo-Olvera, Javier; Siepe, Christoph J.; Li, Zhen Zhou; Lokhande, Pramod V.; Choi, Gun; Ahn, Yong; Chen, Chien-Min; Choi, Kyung-Chul; Van Isseldyk, Facundo; Hagel, Vincent; et al.
Abstract : Study Design: A systematic review of the literature to develop an algorithm formulated by key opinion leaders. Objective: This study aimed to analyze currently available data and propose a decision-making algorithm for full-endoscopic lumbar discectomy for treating lumbar disc herniation (LDH) to help surgeons choose the most appropriate approach [transforaminal endoscopic lumbar discectomy (TELD) or interlaminar endoscopic lumbar discectomy (IELD)] for patients. Summary of Background Data: Full-endoscopic discectomy has gained popularity in recent decades. To our knowledge, an algorithm for choosing the proper surgical approach has never been proposed. Materials and Methods: A systematic review of the literature using PubMed and MeSH terms was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Patient samples included patients with LDH treated with full-endoscopic discectomy. The inclusion criteria were interventional research (randomized and nonrandomized trials) and observation research (cohort, case-control, case series). Exclusion criteria were case series and technical reports. The criteria used for selecting patients were grouped and analyzed. Then, an algorithm was generated based on these findings with support and reconfirmation from key expert opinions. Data on overall complications were collected. Outcome measures included zone of herniation, level of herniation, and approach (TELD or IELD). Results: In total, 474 articles met the initial screening criteria. The detailed analysis identified the 80 best-matching articles; after applying the inclusion and exclusion criteria, 53 articles remained for this review. Conclusions: The proposed algorithm suggests a TELD for LDH located in the foraminal or extraforaminal zones at upper and lower levels and for central and subarticular discs at the upper levels considering the anatomic foraminal features and the craniocaudal pathology location. An IELD is preferred for LDH in the central or subarticular zones at L4/L5 and L5/S1, especially if a high iliac crest or high-grade migration is found.